A Logician's Sidelong Glance at Irony - Reinhard Kahle (Baltic International Yearbook of Cognition, Logic and Communication, 2018)
In "Irony as Expression (of a Sense of the Absurd)" Mitchell Green is presenting an interesting account of communicative irony where ``we express a sense of a situation's absurdity (wackiness, goofiness, etc.).'' In this line of argument, he is questioning the adequateness of irony as meaning-inversion and irony as conversational implicature. In this note, we would like to take the idea of absurdity a little bit further, considering it in its logical sense. As a consequence we can offer a possibility to defend, at least partially, irony as meaning-inversion and conversational implicature.
Keywords: Irony